2021
DOI: 10.3390/diagnostics11101910
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Analysis of DMD Gene Increases the Diagnostic Value of Dystrophinopathies: A Pilot Study in a Southern Italy Cohort of Patients

Abstract: Duchenne/Becker muscular dystrophy (DMD/BMD) is an X-linked neuromuscular disease due to pathogenic sequence variations in the dystrophin (DMD) gene, one of the largest human genes. More than 70% of DMD gene defects result from genomic rearrangements principally leading to large deletions, while the remaining are small nucleotide variants, including nonsense and missense variants, small insertions/deletions or splicing alterations. Considering the large size of the gene and the wide mutational spectrum, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, it has yet to be determined how feasible and time-effective NBS algorithms that involve or do not involve sequencing and repeat CK-MM will be. Additionally, residual clinical sensitivity limitations remain with respect to DMD sequencing; therefore, a subset of DMD cases may test positive with CK-MM screening but will not be detected by current targeted next-generation sequencing tests [ 33 , 34 , 35 ]. Repeat CK-MM testing may reduce the need for sequencing; however, a new specimen procurement for repeat CK-MM testing will incur a separate cost and may delay diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has yet to be determined how feasible and time-effective NBS algorithms that involve or do not involve sequencing and repeat CK-MM will be. Additionally, residual clinical sensitivity limitations remain with respect to DMD sequencing; therefore, a subset of DMD cases may test positive with CK-MM screening but will not be detected by current targeted next-generation sequencing tests [ 33 , 34 , 35 ]. Repeat CK-MM testing may reduce the need for sequencing; however, a new specimen procurement for repeat CK-MM testing will incur a separate cost and may delay diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing (NGS) technologies are increasingly considered more efficient and cost-effective compared to the traditional approach of MPLA/CGH and Sanger sequencing. [ 22 ] NGS allows for multiple genes to be sequenced and analysed in parallel, providing high throughput and ability to detect both large deletions/duplications and small point mutations in coding and non-coding regions, leading to the potential of improved molecular diagnosis of DMD. [ 23 ] Targeted NGS for dystrophinopathies is available as panels of neuromuscular genes, providing additional coverage for the diagnosis of related neuromuscular conditions or mimics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if ES and the other capture-based NGS had been performed, the variant might not have been detected. According to De Palma FDE et al [ 16 ], the authors compared capture-based NGS with traditional methods (MLPA/mPCR/Sanger sequencing) and concluded that capture-based NGS overcomes the limitations of MLPA and Sanger sequences. The capture-based NGS is easy to apply in clinical practice and should be the main strategy for the diagnosis of DMD.…”
Section: Discussionmentioning
confidence: 99%